2018
DOI: 10.1093/pcp/pcy016
|View full text |Cite
|
Sign up to set email alerts
|

A Gatekeeper Residue of ClpS1 from Arabidopsis thaliana Chloroplasts Determines its Affinity Towards Substrates of the Bacterial N-End Rule

Abstract: Proteins that are to be eliminated must be proficiently recognized by proteolytic systems so that inadvertent elimination of useful proteins is avoided. One mechanism to ensure proper recognition is the presence of N-terminal degradation signals (N-degrons) that are targeted by adaptor proteins (N-recognins). The members of the caseinolytic protease S (ClpS) family of N-recognins identify targets bearing an N-terminal phenylalanine, tyrosine, tryptophan or leucine residue, and then present them to a protease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…To understand the substrate specificity of AtClpS1, 60,61 a high‐resolution structure of AtClpS in the presence of bound peptide was needed. Initially, we tried to determine AtClpS1 in complex with an N‐degron using the LC3B fusion technique by attaching the Leu residue at the N‐terminal region of AtClpS1 for easier crystallization 62 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the substrate specificity of AtClpS1, 60,61 a high‐resolution structure of AtClpS in the presence of bound peptide was needed. Initially, we tried to determine AtClpS1 in complex with an N‐degron using the LC3B fusion technique by attaching the Leu residue at the N‐terminal region of AtClpS1 for easier crystallization 62 .…”
Section: Resultsmentioning
confidence: 99%
“…Competition in degradation assays reported that the binding efficiency of AtClpS1 to type‐2N‐degrons was very low and clearly demonstrated the role of the positively charged residue on the surface as a gatekeeper (Figure 1b). 61 Another study conducted binding assays with N‐terminal‐modified green fluorescence protein reporters, and the results showed that AtClpS1 binds strongly to N‐degrons starting with Phe or Trp; however, very intriguingly, the favorable Leu N‐terminus in bacterial ClpS is recognized only weakly by AtClpS1 60,63 . In an effort to quantitatively determine the binding affinity, we measured the K D values between AtClpS1 and several type‐2N‐degron tripeptides using the ITC method (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The poor affinity reported by Ceccarelli and colleagues was attributed to the presence of a socalled "gatekeeper" residue (termed R50, which is the equivalent to what we refer to here as ClpS1 R94 (Fig. 1C,D) based on the amino acid sequence of the full-length protein before processing) at the position equivalent to M40 in E. coli ClpS [36]. As previously described in more detail [30], this arginine is conserved in ClpS1 homologs in angiosperms, but replaced by Glu in ClpS1-like plant and algal species (and Phe in P. falciparum ClpS), reinforcing the question to what extent N-degrons in chloroplasts are the same as in E. coli.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, N‐degrons for chloroplast ClpS1 have yet to be established in vivo or in vitro . A recent study used recombinant ClpS1 to indirectly examine the affinity for several classic N‐degrons through competition in degradation assays with the E. coli ClpAPS system . This suggested that ClpS1 has much lower affinity (~ 20 fold) for the model degrons FR, YL, YK, WF, and LL, and surprisingly, with the lowest affinity to WF.…”
Section: Discussionmentioning
confidence: 99%
“…Amino‐terminal proteomic analysis of the chloroplast stroma indicated that peptides with specific residues at the N‐terminus were underrepresented (Rowland et al ), and reporter proteins in transplastomic plants showed differential stabilities dependent on their Nt‐residues (Apel et al ), suggesting that N‐degron pathway(s) operate in the chloroplast. Recently ClpS1 specificity was investigated in vitro and recognition assays for GFP‐fusion proteins bearing defined Nt‐residues indicated a low specificity for bacterial N‐degrons, but high specificity recognition for Nt‐Phe or Nt‐Trp (Colombo et al ; Montandon et al ). These studies suggest a chloroplast N‐degron pathway with high specificity, though no substrates or transferase activities have yet been identified.…”
Section: Enzymatic Components Of Plant N‐degron Pathwaysmentioning
confidence: 99%